A Social Mindfulness Approach to Understanding Experienced Customer Mistreatment: A Within-person Field Experiment - Song, Yifan; Liu, Yihao; Wang, Mo; Lanaj, Klodiana; Johnson, Russell E.; Shi, Junqi (Academy of Management Journal, 2018)
We apply a social mindfulness lens to understand the phenomenon of perceived customer mistreatment. Recognizing that both recall of prosocial acts and perspective taking invoke the motivation to be mindful in social interactions, we investigated whether these two types of interventions affect customer service employees’ experience of customer mistreatment. Additionally, we investigated whether these two interventions might also buffer the relation of employees’ daily experience of customer mistreatment and their negative mood at the end of the workday. Finally, we examined whether the interventions, via their effects on daily experience of customer mistreatment and afternoon negative mood, could reduce dysfunctional coping responses in the evening (i.e., employee rumination and maladaptive shopping). We conducted a within-person field experiment utilizing a daily experience sampling approach with 94 customer service employees whom we surveyed for 15 consecutive workdays. Consistent with our expectations, both interventions significantly reduced the daily experience of customer mistreatment compared to a control condition. Recall of prosocial action also significantly buffered the positive relation of daily experience of customer mistreatment with afternoon negative mood. Moreover, both interventions had significant indirect effects on dysfunctional coping responses in the evening. We discuss theoretical and practical implications of these findings.